Synthesis of nanocrystalline silicon thin films using the increase of the deposition pressure in the hot-wire chemical vapour deposition technique - S. Halindintwali; D. Knoesen; R. Swanepoel; B.A. Julies; C. Arendse; T. Muller; C.C. Theron; A. Gordijn; P.C.P. Bronsveld; J.K. Rath; R.E.I. Schropp (South African Journal of Science)
Nanostructured thin silicon-based films have been deposited using the hot-wire chemical vapour deposition (HWCVD) technique at the University of the Western Cape. A variety of techniques including optical and infrared spectroscopy, Raman scattering spectroscopy, X-rays diffraction (XRD) and transmission electron microscopy (TEM) have been used for characterisation of the films. The electrical measurements show that the films have good values of photoresponse, and the photocurrent remains stable after several hours of light soaking. This contribution will discuss the characteristics of the hydrogenated nanocrystalline silicon thin films deposited using increased process chamber pressure at a fixed hydrogen dilution ratio in monosilane gas.